Predictive modeling in spine surgery - Malik, Azeem Tariq; Khan, Safdar N. (Annals of Translational Medicine; Vol 7, Supplement 5 (September 10, 2019): Annals of Translational Medicine (Focus on: “Current Trends and Advancements in Spine Surgery”), 2019)
As the cost of healthcare in the United States increases at an unsustainable rate, health-policy leaders are looking towards innovative ways to maximize value in delivery of care. Incorporating technology, such as artificial intelligence/machine-learning, to assist physicians in decision-making and predicting outcomes, on a real-time basis, is a major topic of discussion. While machine learning is gradually pulling traction in the medical community, it still remains a nascent field in the realm of spine surgery. The current review aims to gather current literature discussing the validity and applicability of machine-learning models in spine surgery.